SOME PROBLEMS OF LAST-IN-FIRST-OUT ACCOUNTING. - Davis, Albion R. (The Accounting Review, 1942)
The article discusses some problems of last-in-first-out method of inventory valuation. It must be recognized that accounting for inventories on either a physical or a value basis is not and never can be an exact science. Quantities and values are often no more than approximations or estimates. Regardless of the accounting method used, human judgment is a vital factor in the final results. Consistency of policy relating to inventory valuations within the individual company will still continue to be an important criterion of acceptability to the Treasury Department. Uniformity in detail between different companies in their treatment of inventories is not so necessary. The last-in-first-out amendment is no more of a straitjacket than the income-tax law itself. From its very nature, the last-in-first-out method is appropriate only in those businesses where continuity of related operations and the resultant continuity of inventory position are present. It has no application whatever in a series of short time unrelated, speculative ventures. This is emphasized in the provisions of the law whereby replacements of reductions in inventory below the starting point must be carried on the books at the new cost.